Answer:
c=34
Explanation:
So, our starting equation is: -(14 – 9c) = 4(2c + 5)
and this is how we can solve it:
We move all terms to the left:
-(14-9c)-(4(2c+5))=0
We add all the numbers together, and all the variables
-(-9c+14)-(4(2c+5))=0
We get rid of parentheses
9c-(4(2c+5))-14=0
We calculate terms in parentheses: -(4(2c+5)), so:
4(2c+5)
We multiply parentheses:
8c+20
Back to the equation:
-(8c+20)
We get rid of parentheses:
9c-8c-20-14=0
We add all the numbers together, and all the variables:
c-34=0
We move all terms containing c to the left, and all other terms to the right:
c=34
I know it looks complicated but I do hope this helps! :)